2014
DOI: 10.1007/s10439-014-1029-1
|View full text |Cite
|
Sign up to set email alerts
|

Design, Development and Evaluation of an Inflatable Retractor for Atraumatic Retraction in Laparoscopic Colectomy

Abstract: Laparoscopic colectomy is the gold standard in the treatment of malignant tumours arising in the mucosa of the colon wall. The procedure is performed under general endotracheal anaesthesia and involves establishing a pneumoperitoneum with the patient in the Trendelenburg position. However this position can cause anaesthetic difficulties due to excess blood flow to the head and neck, increased pressure on the diaphragm and increased venous pressure. In the absence of steep head-down positioning, the bowels fall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…There are some other commercially available surgical devices that use the same concept of enlarging the working contact surface area for endoscopic surgery 7,16 ; however, there is little literature outlining the benefits of such devices. A high frictional coefficient of the retractor surface is integral in providing effective and appropriate control of such slippery organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some other commercially available surgical devices that use the same concept of enlarging the working contact surface area for endoscopic surgery 7,16 ; however, there is little literature outlining the benefits of such devices. A high frictional coefficient of the retractor surface is integral in providing effective and appropriate control of such slippery organs.…”
Section: Discussionmentioning
confidence: 99%
“…Although some differences in the concept of organ retraction exist, other studies reported balloon-based retractors for fixation of the bowel to minimize the Trendelenburg position during laparoscopic colectomy. 16 The retractor in this study mainly prioritized controllability, surface friction, and atraumaticity because of the characteristics of the lung and chest cavity, such as limitation of retractor motion, less friction of the lung surface, and sensitivity of the organ. In particular, in the retraction of the lung, the retraction force applied to the lung requires sensitivity to generate delicate tension for the pulmonary artery and vein.…”
Section: Discussionmentioning
confidence: 99%
“…In a preliminary analysis O'Shea et al tested an atraumatic inflatable laparoscopic retractor for retracting the bowel during colectomy [14].…”
Section: Discussionmentioning
confidence: 99%
“…MIS retractors are often unfoldable, like a fan or an umbrella. The efficiency of the retraction can be improved by optimizing the instrument used for retraction, an example of which is an inflatable atraumatic retractor or magnetic anchoring, however, these pose numerous engineering design and application challenges with respect to safe insertion, deployment and retraction [5]. The liver is a delicate tissue [6], often in the way of common MIS procedures, such as cholecystectomy [7].…”
Section: Introductionmentioning
confidence: 99%